Transformational Leadership Analysis in Forming Quality Work Culture at The Gunungsitoli Idanoi Sub-District Office - Gea, Alberman Ekarius; Waruwu, Meiman Hidayat; Telaumbanua, Eliagus; Harefa, Idarni (ProBisnis : Jurnal Manajemen, 2024)
In this study, researchers will conduct an analysis in realizing community empowerment in village programs in the Nazalou Lolowua Village government, Gunungsitoli Alo'oa Subdistrict, In research observations, researchers found that there was dissatisfaction among the village community with the lack of availability and quality of sewing course training organized by the village government. The purpose of this study was to determine the analysis of transformational leadership in the formation of a quality work culture at the Gunungsitoli Idanoi Sub-District Office and the role of transformational leadership in the formation of a quality work culture at the Gunungsitoli Idanoi Sub-District Office. In this study using qualitative methods and data collection techniques using observation, documentation and interviews. The result of this study is that the Camat's leadership is based on an inclusive approach, clear vision, inspirational motivation, intellectual stimulation, and individual attention to employees. The Camat's inclusive approach is reflected in policies and practices that open space for participation of all team members in decision making. Inclusive leadership applied by the Camat of Gunungsitoli Idanoi has a positive impact on the work environment, active participation of team members, motivation, and productivity. This approach is supported by several factors, such as active and equitable participation of all employees in decision-making, a clear vision that leads to improved public services and active community involvement, active involvement of the Sub-district Head with employees, communication of the Sub-district Head's vision and goals, special initiatives for employee development, encouraged creativity and innovation, support for employee intellectual development, individual attention from the Sub-district Head to employees, and employee experience in receiving special attention.